Influence of Tshinguvhu Dialect on grade 8 learners' speaking skills in Tshivenda Home Language, Limpopo Province, South Africa - Mawela, Sonto (My University, 2025)
Tshiguvhu-speaking learners learn Tshivenḓa Home Language in schools as their home language because their dialect is not a standard version of Tshivenḓa. This study focused on the influence of the Tshiguvhu dialect on Grade 8 Tshivenḓa Home Language learners’ oral presentations. The aim of the study was to determine how the Tshiguvhu dialect influences the learners’ speaking skills during oral presentations in a Tshivenḓa Home Language classroom, and finding ways that teachers, learners and the Department of Basic Education can use to alleviate the problem. The study used the qualitative research approach and was conducted in two schools in the Vhembe West District. Data were collected through semi-structured interviews with two Tshivenḓa Home Language teachers and five Tshivenḓa Home Language learners from each school. The researcher also conducted observations at the two schools. Narrative analysis was used to analyse the collected data and elucidated teachers’ and learners’ views on the research problem. The interviews revealed that the two teachers were aware of the influence of the Tshiguvhu dialect on learners’ oral presentations. Tshiguvhu-speaking learners reported that they struggled to speak Tshivenḓa because they only used it at school. Hence the study recommends that teachers should be trained and supported to improve teaching and learning in classes with dialect speakers. Development of language policies that acknowledge existence of dialects and help with strategies to best deal with problems that arise with dialect in the teaching and learning environment.
Thesis (M. Ed. (Language Education)) -- University of Limpopo, 2025
Keywords: Dialect; Tshiguvhu; Tshivenḓa standard language; Home language; Speaking skills; Non-standard language; Venda language -- Study and teaching (Secondary); Dialects; Venda language -- Dialects -- South Africa -- Limpopo